Desafios da intervenção sociológica em prol da inclusão social - Paula Guerra (2004)
In this paper, we present some reflections on the role of sociology as a discipline facilitator of integrated local development dynamics and networking, taking as a stage of reflection of the local reality of Santo Tirso, particularly through contributions from the implementation of the Programa Rede Social. Thus, we will show initiatives, procedures and methodological inroads showing the intervention to promote social cohesion and inclusion carried out by a common disciplinary matrix, resulting from a sharing of experiences in constant restructuring. The approach we intend to do focuses on the mediation of sociologists in the elimination of the mechanisms of poverty and social exclusion, either through cooperation between public and private sectors, either through multisectoral action within an integrated perspective, either, although, through participation and co-responsibility of local groups and communities in order to activate their resources and capabilities, empowering themselves from the processes they face disqualification. Apart from some theoretical aim to demonstrate some indicators of networking and the consequent intervention of sociology as a discipline facilitator of that work, with the backdrop of the reality of the municipality of Santo Tirso, including the implementation of the Programa Rede Social.